2017
DOI: 10.21767/1791-809x.1000535
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Neovascularization on Human Retinal Pigment Epithelium after Hyperbaric Oxygen Therapy

Abstract: Objective: To investigate the neovascularization effect of hyperbaric oxygen (HBO) therapy on human retinal pigment epithelium (REP) cells. Methods:Human REP cells were cultured in vitro, and divided into normoxic control group and hypoxic control group randomly. The experimental groups were then divided into three subgroups via the different HBO pressure, 0.15 MPa exposed group, 0.2 MPa exposed group, and 0.25 MPa exposed group. The experimental groups were exposed to 100% pure oxygen for 60 and 90 minutes tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…Keane found that the strongest correlatian detected between decreased contrast sensitivity and increased total volume of subretinal tissue (Keane, et al, 2010). Previous study by Chao stated that HBOT can decrease the release of TNF-α by RPE cells therefore decreased inflammation (Chao & Chao, 2017). We believed the improvement on contrast sensitivity in our patients were becaused of the decreased inflammation on subretinal tissue by HBOT.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Keane found that the strongest correlatian detected between decreased contrast sensitivity and increased total volume of subretinal tissue (Keane, et al, 2010). Previous study by Chao stated that HBOT can decrease the release of TNF-α by RPE cells therefore decreased inflammation (Chao & Chao, 2017). We believed the improvement on contrast sensitivity in our patients were becaused of the decreased inflammation on subretinal tissue by HBOT.…”
Section: Discussionsupporting
confidence: 49%
“…Although macular light sensitivity improved in HBOT group during one-day of follow up, the trend was not statistically significant. this can be explained from previous study that stated photoreceptor consumed a large amount of oxygen to convert light energy into readable neuronal signals for the brain to translate (Chao & Chao, 2017). The pivotal role of oxygen for photoreceptor survival was reported.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation